Experimental investigation on flow properties of different biomass and torrefied biomass powders. (March 2019) - Xu, Guiling; Li, Menghui; Lu, Ping
Abstract: The utilization of biomass has been increasing in recent years, how to achieve successful feeding of biomass into the different utilization systems is a common problem. Reliable information on flow properties are required for the design of storage, processing and handling equipment. In this paper, the flow properties of four representative agricultural biomass powders (soybean straw, corn straw, rice straw and rice husk) and their torrefied powders were investigated experimentally by two different testing methods (angle of repose test and packing properties test) with a powder synthetic characteristic tester. The effects of mean particle size, particle shape, biomass species and their interaction on different characterization parameters (angle of repose, bulk density, tapped density, Hausner ratio and compressibility index) were investigated. The results of the two different testing methods were compared, and it was found that Hausner ratio and compressibility index cannot always accurately characterize the flowability of biomass powders compared with angle of repose. Meanwhile, the effect of torrefaction pretreatment on the flowability of biomass powders was discussed. The results showed that torrefaction pretreatment can improve biomass powder flowability, however, it cannot change the relative relationship between the flowability of different biomass powders. Highlights: Flow properties of biomass powders useful for design and control were determined. The results of two different testing methods were analyzed and compared. Effects of main physical properties on biomass powders' flowability were discussed. Effect of torrefaction on the flowability of biomass powders was studied.